McKittrick-Wheelock Syndrome Presenting with Acute Kidney Injury and Metabolic Alkalosis: Case Report and Narrative Review - Mireille Caron; Charles-Etienne Dubrûle; François Letarte; Valéry Lemelin; Alexandre Lafleur (Case Reports in Gastrointestinal Medicine)
A rare combination of severe volume depletion and electrolyte imbalance caused by a rectal villous adenoma is often referred to as the McKittrick-Wheelock syndrome. Patients usually seek medical care because of chronic hypersecretory diarrhea and display renal failure, metabolic acidosis, hyponatremia, and hypokalemia. We report the case of a 68-year-old woman who presented with this condition but showed unusual features such as severe hypokalemia and metabolic alkalosis, without diarrhea. She subsequently underwent transanal endoscopic microsurgery (TEMS), an innovative procedure in the management of large rectal adenomas. We also provide a narrative review of the literature on this rare entity.